Stevens-Johnson syndrome induced by combined treatment: carbamazepine and cranial radiation therapy. A case of EMDART? - Anna Waśkiel; Katarzyna Dyttus-Cebulok; Katarzyna Polak-Witka; Małgorzata Pawłowska-Kisiel; Zbigniew Szutkowski; Lidia Rudnicka; Małgorzata Olszewska (Termedia Publishing House, 2017)
Introduction . In 1988, Delattre et al. described the first case of erythema multiforme associated with phenytoin and cranial radiation therapy. In 2004, Ahmed et al. coined the term EMPACT syndrome (Erythema Multiforme associated with Phenytoin And Cranial Radiation Therapy). Case report. A 61-year-old patient with glioblastoma was admitted to our hospital with mucosal and cutaneous involvement diagnosed as Stevens-Johnson syndrome induced by combined treatment consisting of carbamazepine and radiation therapy. The cutaneous and mucosal lesions were successfully treated with prednisone and discontinuation of carbamazepine, chemotherapy and radiation therapy. Conclusions. A discussion is ongoing in the literature about a possible association between radiation therapy, anticonvulsant treatment and Stevens-Johnson syndrome. We present a rare case of Stevens-Johnson syndrome induced by carbamazepine combined with radiation therapy and suggest a new acronym - EMDART (Erythema Multiforme associated with Drug And Radiation Therapy) for the description of this entity, as a wider term compared to EMPACT. The newly suggested term includes all diseases in the spectrum of erythema multiforme (also Stevens-Johnson syndrome and toxic epidermal necrolysis) induced by all drugs (not only phenytoin) in association with radiation therapy in all locations.